Performance analysis of ELM-PSO architectures for modelling surface roughness and power consumption in CNC turning operation - Janahiraman T.V.; Ahmad N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Carbon; Carbon steel; Computer control systems; Electric power utilization; Knowledge acquisition; Learning systems; Machining centers; Particle swarm optimization (PSO); Statistical tests; Steel testing; Turning; Computer numerical control; Extreme learning machine; Machining efficiency; Machining parameters; Mean absolute percentage error; Optimal machining parameters; Performance analysis; Training and testing; Surface roughness